Analisis Pola Makan Mahasiswa Kesehatan Politeknik Negeri Indramayu: Analysis Of The Eating Patterns Of Indramayu State Polytechnic Health Students - Maharani, Ade Ayu; Fitriawati; Kamalia, Nihayatul; Riyani, Ririn; Yanti, Teni Dwi; Nurjanah, Suci (Program Studi Keperawatan Waikabubak, Politeknik Kesehatan Kementerian Kesehatan Kupang, 2024)
Diet is an important factor that will influence nutritional status. Nutritional status is a form of human body health based on food selection and the application of nutrients from these foods to the body. This study aims to analyze the eating habits of Indramayu State Polytechnic nursing students. This article evaluates the eating habits of Indramayu State Polytechnic nursing students using descriptive analysis methods, including using questionnaires to support the analysis. The results obtained were based on a questionnaire which contained 3 categories, namely poor, good and very good. The conclusion obtained from this research is that the majority of Indramayu State Polytechnic nursing students have a good diet.